2002
DOI: 10.1046/j.1432-1033.2002.03123.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two cysteine residues involved in the binding of UDP‐GalNAc to UDP‐GalNAc:polypeptide N‐acetylgalactosaminyltransferase 1 (GalNAc‐T1)

Abstract: Biosynthesis of mucin-type O-glycans is initiated by a family of UDP-GalNAc:polypeptide N-acetylgalactosaminyltransferases, which contain several conserved cysteine residues among the isozymes. We found that a cysteine-specific reagent, p-chloromercuriphenylsulfonic acid (PCMPS), irreversibly inhibited one of the isozymes (GalNAc-T1). Presence of either UDP-GalNAc or UDP during PCMPS treatment protected GalNAc-T1 from inactivation, to the same extent. This suggests that GalNAc-T1 contains free cysteine residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…Two disulfide bonds, C106-C339 and C330-C408, are formed from four invariant cysteine residues. Mutating any of these Cys to Ala significantly reduces expression and abolishes enzyme activity (32). The three remaining catalytic domain Cys are moderately conserved (conservation was determined by comparison of 38 known enzymatically active ppGaNTases described to date) and do not form disulfide bonds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two disulfide bonds, C106-C339 and C330-C408, are formed from four invariant cysteine residues. Mutating any of these Cys to Ala significantly reduces expression and abolishes enzyme activity (32). The three remaining catalytic domain Cys are moderately conserved (conservation was determined by comparison of 38 known enzymatically active ppGaNTases described to date) and do not form disulfide bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Two of these (C212 and C214) have been proposed to interact with UDP-GalNAc based upon chemical modification and mutagenesis studies. Mutating either Cys to Ala reduces activity to 6% and 17%, respectively, of wild-type levels (32). The third Cys (C235) is in a hydrophobic pocket and forms a close contact with M291.…”
Section: Resultsmentioning
confidence: 99%
“…gion. They had several characteristics commonly found in the GalNAc-transferase family: 1) a glycosyltransferase 1 (GT1) motif, a conserved sequence commonly found in glycosyltransferases, 23) 2) a DXH sequence in the GT1 motif, a putative binding site for a sugar donor and/or a metal ion, 24) 3) a Gal/GalNAc-T motif consisting of about 40 amino acid residues, 23) 4) conserved acidic, histidine, and cysteine residues, 23,25,26) and 5) (QXW) 3 repeats, a C-terminal lectinlike domain. 27) We, then, investigated the expression of pt-GalNAc-T. First, the expression of human pt-GalNAc-T in the brain was examined by Northern blot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that these are reduced Cys residues, and are involved in binding with UDPGalNAc. 25) Interestingly, dGalNAc-T3 contains a 39 amino acid residue insertion at the N-terminus of the (QXW) 3 a repeat, which is not found in the other GalNAc-transferases. Moreover, it also has a short insertion (approximately 5-10 amino acid residues) in each repeat of the lectin-like domain.…”
Section: Resultsmentioning
confidence: 99%
“…Tenno et al reported that the modification of mammalian GalNAc-T1 with a Cys-specific reagent, PCMPS, irreversibly inhibited the enzyme with a K i of 0.03 mM and that Cys212 and Cys214, which are C-terminal to the DXH motif, are the sites of the modification and are involved in the binding with UDP-GalNAc. 25) dGalNAc-T3, containing both Cys residues corresponding to mammalian Cys212 and Cys214, was also incubated with increasing concentrations of PCMPS. PCMPS effectively inhibited dGalNAc-T3 with an apparent K i of 0.05 mM (Fig.…”
Section: Resultsmentioning
confidence: 99%